AI Revolution: How Malaysian Firms are Redefining Accounting Performance - Rudzi Munap; Muhammad Izwan Mohd Badrillah; Sagathevaa Subramaniam; Nur Farizan Tarudin (Information Management and Business Review, 2024)
Artificial Intelligence (AI) is the primary force behind the organization's continued sustainability and competitiveness. The rise of AI software, cloud computing-based software and blockchain apps and services, together with the use of accounting information outcomes indicate that computerized accounting has become available to accountants. Even if there are great hopes for the application of AI in the accounting industry, numerous nations with little infrastructure are still lagging in using this type of technology. 88.89% of the 80 questionnaires that were initially issued were returned within a week. As a result, of the 80 questionnaires issued, 75 responses were received in one week, yielding a response return rate of 93.75 percent. Managerial and non-managerial staff members from American Express (Malaysia) Sdn. Bhd, Selangor, Malaysia were chosen as research participants. By employing a sample random sampling approach, a total of 75 legitimate surveys were gathered. The results of the study have shown a positive strong relationship between the level of readiness (AI Software, Cloud technology and Blockchain) and level of adoption (AI Software, Cloud technology and Blockchain) in the accounting industry toward employees’ job efficiency. All eight hypotheses (H1 to H8) showed a significant relationship and were all accepted. The outcome of the moderating effect between working tenure and level of readiness presents a direct impact. However, the level of adoption shows an indirect impact on job efficiency whereas job efficiency shows a direct impact.